Utilization of Geographic Information System(GIS) in Determining the Suitability of Fisheries Locations Cultivation of Freshwater Fish Ponds in South Aceh Regency - Meraty Ramadhini; Arnold Rikardo Sihombing (LPPM Politeknik Aceh Selatan, 2018)
The potential of freshwater aquaculture area in South Aceh has not been optimally pursued; this is due to the limited technological and information capabilities, institutions and funding. The purpose of this study was to map the suitability of freshwater aquaculture land by utilizing the Geographic Information System (GIS) and multi criteria analysis in South Aceh. Determination of land suitability is done through the Multi Criteria Evaluation (MCE) and application of Geographic Information Systems (GIS). The results of the analysis show that the appropriate location (S1) is 81.55% (of the total area sample area) and the location which is not suitable is 18.45% (of the total area sample area). This indicates that the coastal areas of South Aceh have potential freshwater aquaculture areas.